Cholecystectomy with gallbladder bed cautery might be sufficient for T1bN0M0 neuroendocrine carcinoma of gallbladders: Cases report and literature review. Issue 47 (November 2017) - Liu, Wei; Chen, Weijie; He, Xiaodong; Qu, Qiang; Hong, Tao; Li, Binglu
Abstract: Introduction: Neuroendocrine carcinoma was a rare kind tumor in gallbladders. So far, there is no consensus of treatment of the gallbladder neuroendocrine carcinoma. Case presentation: Three patients, 1 male and 2 females, were admitted in our hospital because of right upper quadrant pain. No one complained fever, jaundice, weight loss, or carcinoid syndrome-related symptoms such as diarrhea, flushing, edema, and wheezing. The MRI detected the broad base of gallbladder tumors. However, they refused any radical surgery. We performed a laparoscopic cholecystectomy with gallbladder bed cautery. The pathology results showed that 2 cases were mixed neuroendocrine carcinoma (NECs), and 1 case was a simple NEC. Chromogranin A and synaptophysin were positive in all cases. The pathological TNM stages of all patients were in the T1b N0 M0 stage. The range of Ki-67 was from 40% to 80%. During the at least 26 months' follow-up, there is no case with the recurrence of the carcinoma without any chemotherapy or radiotherapy. Conclusions: Cholecystectomy with gallbladder bed cautery might be enough for treatment of T1b N0 M0 gallbladder neuroendocrine carcinoma.